Comparing Behavioural Problems in Imported Street Dogs and Domestically Reared Danish Dogs—The Views of Dog Owners and Veterinarians - Natascha Munkeboe; Amalie Lohse-Lind; Peter Sandøe; Björn Forkman; Søren Saxmose Nielsen (Animals, 2021)
Street dogs are common in southern and eastern parts of Europe. They are often adopted by people living in North European countries, including Denmark. However, these dogs may experience difficulties adjusting to their new life as companion animals, and this may in turn lead to behavioural problems and complications for owners. The objective of this study was therefore to investigate whether former street (FS) dogs display a higher degree of behavioural problems than dogs reared in Denmark (RD). Two questionnaires were developed. One was distributed to Danish dog owners and resulted in 3020 useful answers. FS dogs were found to display 9 of the 45 listed behaviours more often than RD dogs. All of these behaviours were related to fear, aggression and stress. The second questionnaire was distributed to Danish veterinarians working in small animal practices and resulted in 173 useful answers. The most commonly reported behavioural problems were fear of humans, stress and problems when the dog was left at home alone. The extent of the behavioural problems reported by the veterinarians was much greater than that reported by the dog owners which, at least partly, may be due to fear-induced reactions of the dogs when handled at the veterinary clinic.